Application of DCOR-QFD model for improving the process performance and quality of the product - S. SivadasAniyan, T; R. Pramod, V (International Journal of Engineering and Technology, 2018)
In this case study, DCOR - QFD model has been experimented as a product development process in the forging industry to assess the business process performance of the company, improving the heat treatment process and machining process. The present business process performance characteristics values were calculated using DCOR-1 model. The revised processes for improving the heat treatment process and machining process were identified. In this research, the performance of the integrated DCOR-QFD model was not evaluated in this research. The business process performance of the company using DCOR-1 model and the revised processes for improving the present processes were identified using QFD were calculated separately.